PENGARUH FINANSIAL TEKNOLOGI, LITERASI KEUANGAN, DAN INOVASI BISNIS TERHADAP KEBERLANJUTAN BISNIS UMKM - Dimas Ady Nugroho; A. Khoirul Anam (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the influence of Finansial teknologi, financial literacy, and business innovation on the sustainability of MSMEs fostered by rumah BUMN Jepara. This study uses a quantitative method with a survey method through a Google Form questionnaire which is shared privately and through the official MSME group of rumah BUMN Jepara. The research population amounted to 123 respondents, the data was processed by 106 respondents because the response rate was 86% of the total population, with saturated sampling techniques, and the data was analyzed using SmartPLS 4.0 through the stages of outer model, inner model, and hypothesis tests. The results of the study show that financial technology and financial literacy are proven to have a positive effect on the sustainability of MSMEs, while business innovation has no effect because the innovations carried out are still incremental and have not provided strategic value